Antimicrobial activity and mechanistic insights of AMP-17 against drug-resistant Pseudomonas aeruginosa and its efficacy in wound infection management - Tao, Ruyu; Tian, Chunren; Su, Ting; Cai, Ruxia; Song, Dongxu; Zhao, Na; Lei, Yuansan; Jiao, Zhenlong; Guo, Guo (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionChronic wound infections caused by drug-resistant bacteria have emerged as a global health challenge, affecting millions of patients annually and imposing a substantial economic and societal burden. However, current therapeutic approaches exhibit limited efficacy in treating drug-resistant wound infections, highlighting an urgent need for novel treatment strategies. Our previous studies have demonstrated that the Musca domestica antimicrobial peptide-17 (AMP-17) exhibits potent antibacterial activity, suggesting its potential as a promising anti-infective agent. Building on these findings, the present study isolated clinically relevant drug-resistant Pseudomonas aeruginosa (P. aeruginosa) strains and employed a combination of in vitro and in vivo experiments to systematically evaluate the efficacy of AMP-17 in combating drug-resistant infections and promoting wound healing. Furthermore, we preliminarily investigated the underlying mechanisms involved.Materials and methodsMIC/MBC of AMP-17 against drug-resistant P. aeruginosa were determined by microbroth dilution and agar spot assays. Biofilm inhibition/eradication was assessed via crystal violet staining, while swarming motility was tested on semi-solid agar. A murine wound infection model was established to evaluate the in vivo antimicrobial activity of AMP-17, and the levels of relevant cytokines were measured to preliminarily explore its anti-inflammatory mechanisms. Furthermore, the effects of AMP-17 on membrane permeability, proton motive force (PMF), pyocyanin production, and reactive oxygen species (ROS) levels in drug-resistant Pseudomonas aeruginosa were systematically investigated using scanning electron microscopy (SEM), confocal laser scanning microscopy (CLSM), and a multifunctional fluorescence microplate reader.Results and discussionThe results of this study demonstrate that AMP-17 exhibits significant antimicrobial activity against drug-resistant Pseudomonas aeruginosa. The underlying mechanisms primarily involve disruption of bacterial membrane integrity, alteration of proton motive force (PMF), increased intracellular ROS levels, and inhibition of bacterial motility, ultimately leading to bacterial cell death. Additionally, AMP-17 shows promising efficacy in inhibiting biofilm formation and eradicating mature biofilms of drug-resistant P. aeruginosa. In a murine wound infection model, AMP-17 displayed potent in vivo antimicrobial activity, significantly reducing bacterial load and downregulating pro-inflammatory cytokine expression, thereby effectively promoting wound healing. Collectively, these findings highlight the potential of AMP-17 as a promising therapeutic agent for combating drug-resistant P. aeruginosa infections and enhancing wound healing.